LUCAS Soil Biodiversity and LUCAS Soil Pesticides, new tools for research and policy development. (18th September 2022) - Orgiazzi, Alberto; Panagos, Panos; Fernández‐Ugalde, Oihane; Wojda, Piotr; Labouyrie, Maëva; Ballabio, Cristiano; Franco, Antonio; Pistocchi, Alberto; Montanarella, Luca; Jones, Arwyn
Abstract: The European Green Deal puts a healthy environment at the core of policy‐making initiatives in the European Union (EU). Soil, due to its nature, is a central actor to be considered when developing and implementing actions in many areas, from biodiversity and agriculture to climate and pollution. New means for monitoring the impact of decisions taken in these sectors are needed. The Land Use and Coverage Area frame Survey (LUCAS modules of Soil Biodiversity and Pesticides provide both policy‐makers and the research community with tools in this direction. The first component corresponds to the largest analysis of soil biodiversity across the EU through molecular biology techniques. The second component is the most extensive harmonised pan‐European assessment of pesticide residues in agricultural soils. Specific features, together with policy and research potential of these instruments for achieving Green Deals targets under the Biodiversity 2030 Strategy, the Farm to Fork Strategy and the Zero Pollution Action Plan, are presented. All generated data are made available to the public through the EU Soil Observatory and European Soil Data Centre. Highlights: LUCAS Soil Biodiversity is a monitoring survey of biodiversity in the European Union. LUCAS Soil Pesticides is a monitoring survey of pesticide residues in the European Union. Protocols and data from LUCAS Soil Biodiversity and Pesticides are open access. LUCAS Soil Biodiversity and Pesticides can support policy and research development.